O uso do Geogebra no estudo de trigonometria. - MIRANDA, Rafael Santos (2021)
In this work we presente the use of the dynamic geometry software “ geogebra” in the content tigonometry in high school, with the application of contents in a dynamic way for better visualization and interpretation of the function graphs. We hope that present work can be used teaching-learning processo of trigonometry. Certain unexpected situations that arise in the classroom can be explained with the support of appripriate software.